Learning Management System - Schoolearn Based on Moodle for Creating Virtual Classes for SMP Negeri 25 Kab. Barru: Learning Management System - Schoolearn Berbasis Moodle Untuk Pembuatan Kelas Virtual Bagi Guru SMP Negeri 25 Kab. Barru - Rusli, Rusli; Ahmar, Ansari Saleh; Rahman, Abdul; Musa, Hastuty (Yayasan Ahmar Cendekia Indonesia, 2024)
The Ipteks for Community activity was carried out at SMP Negeri 25 Barru, Barru Regency, Bojo District, South Sulawesi Province. The objectives of this activity are to: (1) Increase teachers' knowledge in managing LMS-based online learning; (2) Increase teachers' awareness and knowledge about the importance of multimodal learning management; (3) Increase teachers' insights, abilities, and skills in utilizing moodle LMS-based web learning management; and (4) Reduce the number of teachers who do not use blended learning in this 21st century computing era. Partner problems are: (1) the lack of knowledge of junior high school teachers in processing LMS-based online learning; (2) the absence of LMS facilities managed by the school; and (3) the lack of digital-based teacher learning tools even though the current era is a digital era. The method used is counseling and teaching, discussion, and training in collaboration between the implementer and the first partner. This method was carried out to all teachers of SMP Negeri 25 Barru and Mathematics Teachers who joined MGMP Mathematics SMP Barru district, who were trained for 1 day face-to-face and mentored through WA groups and then gradual evaluation and monitoring were carried out periodically for 2 months. The results obtained are: (1) Teachers' knowledge in managing LMS-based online learning is getting better; (2) Teachers' awareness and knowledge about the importance of learning management. (3) Teachers' insights, abilities, and skills in utilizing moodle LMS-based web learning management; and (4) The number of teachers implementing blended learning has increased, (5) teachers have had virtual classes as a complement to conventional classroom-based classes, so that teachers can teach their students without being limited by space and time, meaning that teachers can teach students according to the place and time provided by their students to learn when outside school hours. Abstrak Kegiatan Ipteks bagi Masyarakat dilaksanakan di SMP Negeri 25 Barru Kabupaten Barru Kecamatan Bojo, Provinsi Sulawesi Selatan. Tujuan kegiatan ini adalah untuk: (1) Meningkatkan pengetahuan guru dalam mengelola pembelajaran online berbasis LMS; (2) Meningkatkan kesadaran dan pengetahuan pada guru tentang pentingnya pengelolaan pembelajaran multimoda; (3) Meningkatkan wawasan, kemampuan, dan keterampilan guru dalam memanfaatkan mengelola web learning berbasis LMS moodle; dan (4) Mengurangi jumlah guru yang tidak menggunakan blended learning di era komputasi abad 21 ini. Permasalahan mitra adalah: (1) Kurangnya pengetahuan guru SMP dalam pengolahan pembelajaran online berbasis LMS; (2) tidak adanya fasilitas LMS yang dikelola oleh pihak sekolah; dan (3) kurangnya perangkat pembelajaran guru berbasis digital padahal era saat ini adalah era digital. Metode yang digunakan adalah penyuluhan dan pengajaran, diskusi, dan pelatihan secara kolaborasi antara pelaksana dengan mitra pertama. Metode ini dilaksanakan kepada semua guru SMP Negeri 25 Barru dan Guru Matematika yang bergabung pada MGMP Matematika SMP kabupaten barru, yang dilatih selama 1 hari tatap muka dan dilakukan pendampingan melalui grup WA dan selanjutnya evaluasi bertahap dan monitoring dilakukan secara berkala selama 2 bulan. Hasil yang diperolah adalah: (1) Pengetahuan guru dalam mengelola pembelajaran online berbasis LMS semakin baik; (2) Kesadaran dan pengetahuan pada guru tentang pentingnya pengelolaan pembelajaran multimoda; (3) Wawasan, kemampuan, dan keterampilan guru dalam memanfaatkan mengelola web learning berbasis LMS moodle; dan (4) Jumlah guru yang melaksanakan pembelajaran secara blended bertambah, (5) guru telah memiliki kelas virtual sebagai pelengkap kelas konvensional berbasis kelas, sehingga guru-guru dapat membelajarkan siswanya tanpa dibatasi lagi oleh ruang dan waktu, artinya guru-guru dapat membelajarkan siswa sesuai dengan tempat dan waktu yang disediakan oleh siswanya untuk belajar saat dilaur jam sekolah.